2010
DOI: 10.1029/2009wr007850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of permeability on CO2 trapping mechanisms and buoyancy‐driven CO2 migration in saline formations

Abstract: [1] We present the results from a series of numerical simulations to explore systematic k heterogeneity effects on both CO 2 trapping mechanisms and buoyancy-driven CO 2 migration. For this purpose, we generated various permutations of two-dimensional numerical models of subsurface porous media: homogeneous, random, homogenous with a low-permeability (k) lens, and isotropically/anisotropically correlated k fields. For heterogeneous cases, we used a sequential Gaussian simulation technique to generate ten reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 81 publications
5
41
0
Order By: Relevance
“…Increasing the permeability of the storage 556 site without changing the porosity results in the plume diameter increasing. This result is supported 557 by the findings of Han et al (2010) who showed that a larger area of the storage site is swept by CO 2 558 when the formation permeability is increased. Similarly Jahangiri & Zhang (2011) found that the 559 overall plume spread in all directions is increased when formation permeability is higher.…”
Section: Pressure Buildup and Plume Diameter 531supporting
confidence: 80%
“…Increasing the permeability of the storage 556 site without changing the porosity results in the plume diameter increasing. This result is supported 557 by the findings of Han et al (2010) who showed that a larger area of the storage site is swept by CO 2 558 when the formation permeability is increased. Similarly Jahangiri & Zhang (2011) found that the 559 overall plume spread in all directions is increased when formation permeability is higher.…”
Section: Pressure Buildup and Plume Diameter 531supporting
confidence: 80%
“…A detailed description of the GEM simulator is discussed in previous studies of subsurface CO 2 plume behavior (Kumar et al 2005;Bryant et al 2008;Saadatpoor et al 2009;Han et al 2010a). …”
Section: Numerical Simulation Settingsmentioning
confidence: 99%
“…Bryant et al (2008) and Saadatpoor et al (2009) showed that the capillary pressure scaled with spatially correlated permeabilities in heterogeneous formations may lead to channeling of vertically migrating CO 2 plumes and impact both the overall configuration of CO 2 plumes and the degree of CO 2 trapping. Ide et al (2007), Flett et al (2007), Green and Ennis-King (2010), and Han et al (2010a) performed more detailed analyses of CO 2 trapping mechanisms including the time-scale of convective mixing in various degrees of subsurface heterogeneity (e.g., permeability variance, correlation length, and amount of shale fraction/thickness). Different from the studies associated with subsurface heterogeneity, Juanes et al (2006) performed numerical simulations at reservoir scales to understand how the changes in engineering parameters such as injection rate, injection ratio of water and CO 2 (alternating water injection), and bottom-hole pressure may influence residual CO 2 trapping.…”
mentioning
confidence: 99%
“…Permeability heterogeneity is a critical factor influencing CO 2 migration and trapping in saline aquifers. The effect of permeability heterogeneity on the transport and trapping behaviors of CO 2 has been studied since about a decade ago . For a reservoir formed in a depositional environment, permeability heterogeneity can stem from both the spatial distribution of depositional faces and the variations in grain size distributions within each face .…”
Section: Introductionmentioning
confidence: 99%